CRACKER BUSINESS ANALYSIS IN KEDUNG REJO VILLAGE JABON DISTRICT, SIDOARJO REGENCY - Soesanto Soesanto; Mega D. Novita (Jurnal Ekonomi, 2022)
The contribution of the industrial sector indicates that there are small industries, such as home industries in Sidoarjo. Industries in Sidoarjo such as songkok, woven sarongs, crackers, processed milkfish, and others. One of the famous industries in Sidoarjo is the white cracker industry, which is in Village Bulurejo, Subdistrict Sidoarjo. The research aims to analyze and describe the business profile of white crackers, costs and revenues, as well as how to develop a white cracker business, in Bulurejo Village, Sidoarjo Regency. The research uses qualitative methods and uses interviews and observations as primary data collection tools. This study uses the calculation tool Revenue Cost Ratio and Return OF Investment as an indicator of business feasibility of white crackers. The data was obtained from 5 informants of white cracker business owners. From the research of white cracker entrepreneurs, the average age of business owners making white crackers in Bulurejo Village is around 40-50 years. The level of education they go to is mostly elementary and junior high school. The effort of white crackers that they took for quite a long time about 10-20 years. The size of the place for producing white crackers in one room has an average length of 22 meters and a width of 20 meters. The number of white crackers produced as much as 200,000-250,000 white crackers / month. White cracker business generates ROI with an average monthly capital issued of 55,857,226/month which generates an average ROI of 10.4% and generates an average R/C of 1.10 which means > 1, thus the average effort of making white crackers. While the average profit obtained from 5 white cracker entrepreneurs in Bulurejo Village Village amounted to 5,705,273.